2015
DOI: 10.4238/2015.march.13.2
|View full text |Cite
|
Sign up to set email alerts
|

Association between the LXRα polymorphism and stroke in a Chinese population

Abstract: ABSTRACT. We examined the relationship between the liver X receptor α gene (LXRα) polymorphism and the susceptibility to stroke. We utilized the single fluorescent-labeled probe technique to detect the genotype of rs12221497 in the LXRα gene in 400 stroke patients and 400 healthy control subjects. The difference in genotype distribution between the 2 groups was analyzed using the chi-square test. Serum lipids and glucose levels between the different genotypes were also compared. We found that the risk of strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Polymorphisms of genes that involve in the regulation of lipid metabolisms such as apolipoprotein E (apo E), cholesteryl ester transfer protein (CETP), and liver X receptors (LXR) have been reported to correlate with the efficacy of statin and susceptibility to cardiovascular disease. [6][7][8][9][10][11] Several studies have revealed that the genetic variants of the pharmacokinetics-related genes result in the diversity of statin efficacy among individuals. [12][13][14] Since statins have the primary site of action and metabolism in the liver, where they inhibit HMG-CoA reductase, the genetic variations of Phase I and II drug-metabolizing enzymes and drug transporter genes may have a critical role in the concentration of statins within hepatocytes and plasma, and consequently clinical efficacy to the treatment of statin.…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms of genes that involve in the regulation of lipid metabolisms such as apolipoprotein E (apo E), cholesteryl ester transfer protein (CETP), and liver X receptors (LXR) have been reported to correlate with the efficacy of statin and susceptibility to cardiovascular disease. [6][7][8][9][10][11] Several studies have revealed that the genetic variants of the pharmacokinetics-related genes result in the diversity of statin efficacy among individuals. [12][13][14] Since statins have the primary site of action and metabolism in the liver, where they inhibit HMG-CoA reductase, the genetic variations of Phase I and II drug-metabolizing enzymes and drug transporter genes may have a critical role in the concentration of statins within hepatocytes and plasma, and consequently clinical efficacy to the treatment of statin.…”
Section: Introductionmentioning
confidence: 99%